Compost for Your Seeds: Implementation Strategies for Environmental Education in Chile from the Eric Taxonomy - Rojas-Andrade, R; Prosser-Bravo, G (Routledge, 2025)
The increasing interest in climate change and environmental education has highlighted the importance of strategies to enhance the adoption, implementation, and sustainability of these initiatives. However, the field of environmental education has not extensively explored implementation strategies, despite the existence of frameworks and taxonomies. This study aims to address this gap by identifying strategies suggested by environmental education professionals in Chile. A total of 91 participants responded to an online survey that included open-ended questions. Through content analysis, 24 categories aligned with existing frameworks and 7 categories emerging from the local context were identified. These categories were organized in a descending order, revealing the prominence of scale-up, process, capacity-building, integration, and dissemination strategies. While strategies from established frameworks were found, the study also highlights the emergence of strategies specific to the environmental education field, contextual factors, and the implementation phase of environmental education in Chile. © 2024 Informa UK Limited, trading as Taylor & Francis Group.